Phytochemicals health promotion and therapeutic potential - Carkeet, Colleen (CRC Press, 2013)
"An examination of foods, botanicals, and phytochemicals as they relate to the prevention of age-related chronic diseases, this book discusses herbs and spices in cancer prevention; wine, phenolics, and cancer; anthocyanins in cardiovascular health; anti-inflammatories; skin photoprotection; beny phytochemicals; green tea catechins; and cognitive function in the elderly. The book begins with an overview of phytonutrients in human health and disease, and covers chronic disease prevention, bone and joint health, skin health, obesity and metabolism, and brain health. The final chapter describes an analytical technique 'proving very powerful in phytonutrient research in humans"--Provided by publisher.
Keywords: Materia medica, Vegetable -- Congresses.; Chronic diseases -- Congresses.; Plant extracts -- Congresses.; elektronické knihy; electronic books